Protease-activated receptor-1 deficiency protects against streptozotocin-induced diabetic nephropathy in mice - Waasdorp, Maaike; Duitman, JanWillem; Florquin, Sandrine; Spek, C. Arnold (Scientific reports, 2016)
Endogenously administered activated protein C ameliorates diabetic nephropathy (DN) in a protease-activated receptor-1 (PAR-1)-dependent manner, suggesting that PAR-1 activation limits the progression of DN. Activation of PAR-1 in fibroblast-like cells, however, induces proliferation and extracellular matrix production, thereby driving fibrotic disease. Considering the key role of mesangial proliferation and extracellular matrix production during DN, PAR-1 may in fact potentiate diabetes-induced kidney injury. To determine the net effect of PAR-1 in DN, streptozotocin-induced DN was studied in wild type and PAR-1 deficient mice. Subsequent mechanistic insight was obtained by assessing profibrotic responses of mesangial and tubular epithelial cells in vitro , following PAR-1 stimulation and inhibition. Despite having similar glucose levels, PAR-1 deficient mice developed less kidney damage after induction of diabetes, as evidenced by diminished proteinuria, plasma cystatin C levels, expansion of the mesangial area, and tubular atrophy. In vitro , PAR-1 signaling in mesangial cells led to increased proliferation and expression of matrix proteins fibronectin and collagen IV. Conversely, a reduction in both proliferation and fibronectin deposition was observed in diabetic PAR-1 deficient mice. Overall, we show that PAR-1 plays an important role in the development of DN and PAR-1 might therefore be an attractive therapeutic target to pursue in DN.